Les députées blogueuses, des hommes politiques comme les autres ? - Marie Neihouser (Communication)
The author draws on a comprehensive sample of French political blogs (3,509 sites). By carefully qualifying the sociodemographic characteristics of the bloggers, the politicization of each blogger, and a set of data attached to each blog and to the digital activity of each blogger, the author classifies the blogs according to the position and political leanings of their authors. In all the study looks at 120 blogs by female members of parliament and 312 by male members. Contrary to current differentialist theses, the author finds that male and female MPs have generally similar blogging practices.